A Retrospective Forensic Review of Unexpected Infectious Deaths. (15th February 2019) - Sehgal, Prateek; Pollanen, Michael; Daneman, Nick
Abstract: Background: There exists a knowledge gap in identifying the spectrum of infectious pathogens and syndromes that lead to fulminant decline and death. The aim of this study was to better characterize patient-, pathogen-, and disease-related factors in the phenomenon of unexpected infectious deaths. Methods: We conducted a population-based, retrospective cohort study of all community-based, unexpected infectious deaths in Ontario, Canada between January 2016 and December 2017. Patient-related information, infection-related information, and circumstances around the death were extracted for each case to facilitate descriptive analyses. Results: Of the 7506 unexpected deaths over the study period, 418 (6%) were due to infectious diseases. Bacterial pneumonia (43%) was the most common infectious syndrome, followed by disseminated infection with no clear focus (12%), peritonitis (10%), myocarditis (6%), and pyelonephritis (5%). A pathogen was identified in 210 cases (50%), with the most common being Staphylococcus aureus (n = 35), Streptococcus pneumoniae (n = 30), Streptococcus pyogenes (n = 25), Klebsiella spp. (n = 23), and Escherichia coli (n = 19). Prodromal symptoms were present in 68% of persons before death, with a median (interquartile range) duration of only 1.0 (0.0–4.0) days; just 30% of those who died had had recent healthcare contact before their death. Conclusion: Infectious diseases have the capacity to cause fulminant decline and death. The most common cause of unexpected infectious death is bacterial pneumonia, with a predominance of gram-positive bacteria. Given the rapidity of these deaths, preventing a majority of them would require upstream strategies to reduce infection susceptibility and transmission. Abstract : This population-wide cohort study highlights the phenomenon of unexpected deaths due to infectious disease, with respect to the key pathogens involved, the most prominent clinical syndromes, characteristics of those who died, and opportunities and challenges for prevention.